Studenten strooien hete centen voor het volk. Stedelijke identiteit en de geschiedenis van een omstreden herinnering in Leiden (1841-2016) - Van der Steen, Bart; Burger, Peter (TSEG - The Low Countries Journal of Social and Economic History, 2018)
Legend has it that students in the Dutch university town of Leiden used to throw coins in the street for the less well-off citizens. Picking up the coins, these risked burning their fingers: the students had heated the coins in a skillet. This story is told as emblematic for the social and cultural differences dividing laborers and students, or, more generally, ‘town and gown’. Opinions differ about the veracity of the story and the time period during which this prank was perpetrated. Our study of this local legend is based on local newspapers and other digitized sources that have recently become available, allowing us to trace the story over a time period that spans the years 1841-2016. The hot coins prank is related to a more benign, internationally known custom during which both throwers and throwees know what to expect. In the Netherlands, stories about the prank have become associated in particular with the town of Leiden, becoming more prominent during the 20th century, after the prank itself was no longer performed. We read the hot coin legend in the context of collective memory and urban identity: over the course of two centuries, various social groups have used the story as a boundary marker between in-group and out-group, and more broadly as a means to reflect on the shifting identity of the town. During the years of urban renewal in the second half of the twentieth century, Leiden transformed from an old, poor, industrial town into a modern, affluent urban centre that touts itself as a ‘city of knowledge’. Rhetorically, the hot coin legend is presented as a test case for social cohesion: did Leiden truly leave behind its divided history?